1. The problem statement, all variables and given/known data I'm asked to prove that Et - p⋅r = E't' - p'⋅r' 2. Relevant equations t = γ (t' + ux') x = γ (x' + ut') y = y' z = z' E = γ (E' + up'x) px = γ (p'x + uE') py = p'y pz = p'z 3. The attempt at a solution Im still trying to figure out 4 vectors. I get close to the solution but I have some values hanging around. For the first two terms, E and t, i just multiple them out. (γ (E' + up'x))(γ (t' + ux') ) Next I work with the p and r. The way i understand them is that that p is equal to the three different equations i have listed for px,py, and pz. And the same thing for r but with x,y, and z. Im guessing that because i don't a lorentz transformation formula for just p or r. I then multiply px with x, py with y, and pz with z. adding the products of each along the way. am i on the right track? I start canceling terms but ultimately I'm left with a γ2ut'uE' and γ2ux'up'. I'm also left with a bunch of γ2's.